Bacterial pollution in Molluscs Arch Clam, Orbicularia orbiculata and Blood Cockle, Anadara granosa of Pahang estuary, Malaysia - Khan Chowdhury, Ahmed Jalal; Musa, Najiah; Mahfuz, Fathiyah; Yunus, Kamaruzzaman; Omar, Muhammad Nor; Sarker, Mohammad Nurul Amin; Jaswir, Irwandi (Asian Network for Scientific Information, 2009)
A study was conducted on physico-chemical parameters and bacterial pollution in Orbicularia orbiculata (Wood, 1828) and Anadara granosa (L.) at Pahang estuary from January to February 2009. The temperature was ranged from 28.00-29.87°C, pH 7.79-8.10, specific conductivity 51.49-55.89 mS cm-1, salinity 18.74-30.10 ppt., TDS 33.63-39.59 g L-1, DO 6.80-7.50 mg L-1. The nitrate concentration was found to be highest at Station 3 (14.09 μg at N-l) and lowest at Station 2 (7.04 μg at N-l). The nitrite concentration showed highest concentration at Station 4 (7.07 μg at N-l) and lowest concentration at Station 2 (1.67 μg at N-l). Whilst the phosphate content was higher (10.78 μg at N-l) at Station 3 and lowest at Station 2 (2.34 μg at N-l). A total of 60 Orbicularia orbiculata and 40 Anadara granosa samples were subjected to microbiological analysis. The bacteria were isolated using non selective agar such as TSA agar and selective agar before they were identified using conventional methods in combination with API identification kit. A total of nine bacterial species were identified from Orbicularia orbiculata. They were Escherichia coli., Aerococcus viridans 1, Aerococcus viridans 2, Gemella morbillorum, Kocuria varians, Micrococcus sp., Pseudomonas aeruginosa, Staphylococcus sciuri, Streptococcus pneumoniae. Whilst, Nineteen bacterial species were identified in Anadara granosa such as Aeromonas hydrophila group 1, Aerococcus viridians 1, Aerococcus viridans 2, Chromobacterium violaceum., Enterobacter gergoviae, Erwinia sp., Escherichia coli, Enterococcus avium, Gemella morbillorum, Kluyvera sp., Vibrio fluvialis, Vibrio cholerae, Vibrio parahaemolyticus, Lactococcus lactis, Leuconostoc sp., Staphylococcus capitis, Staphylococcus lentus, Staphylococcus epidermidis, Staphylococcus xylosus. The finding indicates that the edible mollusc of Pahang estuary was polluted with pathogenic bacteria which could be harmful for human consumption.